PENDEKATAN HOLISTIK PADA Tn. S LANSIA DRIVER TRUK DENGAN TINEA PEDIS - Diana Mayasari; Muhammad Fakih Abdurrohman (Medula, 2021)
Occupational skin disease is one of the occupational diseases that occur frequently in the community, and is the second most occupational disease in Europe after musculoskeletal injuries.1 Tinea pedis or also known as athlete's foot is a superficial fungal infection of the skin. feet that often occur in cases of dermatophytosis in general today.2 Tinea pedis infection also attacks various levels of work, especially jobs that require wearing tight and closed shoes, increased moisture due to sweat, mechanical rupture of skin, and exposure to fungi are predisposing factors causes tinea pedis.3 It is estimated that about 70% of the population worldwide has been infected with tinea pedis.Patient Mr. S 65 years old with a complaint of red scaly patches accompanied by itching on both toes since 3 weeks ago. Individual factors that play a role in the form of patients often wearing tight and closed shoes. From the physical examination, it was found that the picture of fungal infection was in the form of reddish spots with scales on top with central healing and active margins. There are no factors outside of work that contribute to the onset of symptoms. From these results, the occupational disease of Tinea pedis was enforced due to the use of tight and closed shoes while working. The treatment given is in the form of medical and non-medicamentous with the main focus to cure and prevent recurrence.